Practitioner perspectives of domestic abuse and women over 45 - Carthy, Nikki L. (European journal of criminology, 2018)
Low reporting of domestic abuse among women 45 and older has resulted in the needs of those women becoming forgotten among service development. We interviewed 18 practitioners to explore their experiences of working with this client group. Descriptive thematic analysis identified two core themes: an uncertain future as a barrier to seeking support, and a lack in knowledge of domestic abuse and service provision. There is still a long way to go: (i) to break down social barriers for middle-aged and older women to seeking support; and (ii) to acknowledge domestic abuse among professionals and the public. The research draws on a practitioner voice alongside reflections on one of the UK’s first safe houses aimed at supporting women 45 and over.